2013
DOI: 10.1097/bpo.0b013e318278484f
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Septic Arthritis and Osteomyelitis in Children

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
2
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 14 publications
7
54
2
1
Order By: Relevance
“…The high concurrency of osteomyelitis observed in this series is not surprising [5]. Several studies have shown a low bacterial recovery rate around 33-37% [1,2,6], which are much lower than that found in our study where the cultures resulted in a high return rate (70%).…”
Section: Discussioncontrasting
confidence: 55%
“…The high concurrency of osteomyelitis observed in this series is not surprising [5]. Several studies have shown a low bacterial recovery rate around 33-37% [1,2,6], which are much lower than that found in our study where the cultures resulted in a high return rate (70%).…”
Section: Discussioncontrasting
confidence: 55%
“…Although there has been dramatic change in the prognosis and disease course in acute osteoarticular infections during the last century, acute osteoarticular infections are still a source of morbidity and even mortality, especially when concurrent septic arthritis and osteomyelitis are initially overlooked [6,10,11]. In our study, the presence of a coexisting joint effusion in the setting of metaphyseal osteomyelitis was found to represent concurrent septic arthritis in a majority of cases (75%) with a P-value of <0.0001.…”
Section: Discussionmentioning
confidence: 76%
“…Additionally, the neonatal periosteum is thinner and more likely to perforate, spilling infection into the joint and adjacent soft tissues [14]. McCarthy et al [11] quote a rate of 76% and, more recently, Montgomery et al [6] quote a rate of 78% for concurrent septic arthritis in the setting of neonatal osteomyelitis. In our study population, the percent of patients younger than 2 years with coexisting septic arthritis was 44%; however, children in this age group only represented 20% of the overall population.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations